Cache Simulator - Razi AL-sayed; Mohammed Abu-jamous (My University, 2005)
This thesis describes the design and implementation of the MLCacheSim, a cache simulator program. This product is designed to give the computer researchers, designers and students the ability to monitor cache systems behavior and determine the various cache systems performance. The MLCacheSim is implemented using ANSI / ISO C++ programming language. This thesis introduces this as The Simulator Engine implementation.A final analysis shows that many of the core modules are functional in the final implementation and that a fully operational Simulator is achieved.

This thesis describes the design and implementation of the MLCacheSim, a cache simulator program. This product is designed to give the computer researchers, designers and students the ability to monitor cache systems behavior and determine the various cache systems performance. The MLCacheSim is implemented using ANSI / ISO C++ programming language. This thesis introduces this as The Simulator Engine implementation.A final analysis shows that many of the core modules are functional in the final implementation and that a fully operational Simulator is achieved.
Cache Simulator